Development, evaluation and mechanicals stimulation of 3D bone cancer metastases models - Yong, Kim Yeow (2016)
Prostate cancer related bone metastasis is one of the leading causes of death in men, commonly associated with increased osteoclastic activity at the affected site, causing bone loss and osteoporosis. Numerous clinical studies have shown that exercise could reduce tumour growth and reduce the risk of contracting cancer. In this study, we developed metastatic cancer models consisting of co-cultures of RFP transfected-prostate cancer cells and mesenchymal stem cells. Cancer cell proliferation on 2D and 3D substrates was studied and characterized using fluorescence microscopy and qRT-PCR. This was followed by application of cyclic mechanical loading on the 3D cancer models and analysis of associated effect on cellular proliferation. Results showed that cancer cell proliferation rates in 3D models are lower than the 2D models. Cyclic compressive strains (2200μƐ, 1 Hz) on 3D models led to a decrease in H2B-RFP gene expression, which could indirectly indicate a reduction in the cancer cell numbers. To increase the physiological relevance of 3D cancer models to in vivo models, 3D tumour spheroids have been considered in the design of 3D metastatic cancer models. Process parameters to fabricate PC-3 multicellular tumour spheroids were optimized and characterized. Spheroids with diameter > 500μm demonstrated declining growth rates and experienced structural instability. Quantification of spheroid growths using gene expression means and image-based diameter measurements were found to be statistically equivalent to each other. Results suggest that image-based analysis could replace invasive quantification methods as a form of non-destructive method to measure tumour growth.